2006
DOI: 10.1590/s1678-77572006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2% iodine disinfecting solution on bond strength to dentin

Abstract: Introduction:Disinfection of dentin surfaces is desirable so long as it does not interfere with subsequent bonding of adhesive resins.Objective:To test the null hypothesis that bond strengths to dentin are not affected by previous application of an iodine disinfecting solution.Materials and Methods:Twenty-four extracted non-carious molars were selected. Occlusal enamel was removed producing a flat dentin substrate. Test teeth were all treated with 2% Iodine disclosing/disinfecting solution (I2DDS) for 20 sec a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…Iodine has the ability to destroy the bacterial cell by attacking its proteins, nucleotides, and fatty acids. 90 It has been reported to disclose and eliminate bacteria in plaque, 91,92 and their effectiveness against cariogenic bacteria has been also documented.…”
Section: Antimicrobial Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine has the ability to destroy the bacterial cell by attacking its proteins, nucleotides, and fatty acids. 90 It has been reported to disclose and eliminate bacteria in plaque, 91,92 and their effectiveness against cariogenic bacteria has been also documented.…”
Section: Antimicrobial Effectivenessmentioning
confidence: 99%
“…87,91,96,97 da Silva et al 91 found the effect of 2% I2DDS on the µTBS of different adhesive systems to be materialspecific. They found µTBS to be significantly decreased for ethanol-and water-based adhesive systems (Single Bond, Clearfil SE Bond, and Opti-Bond Plus).…”
Section: Effects On Restorative Treatmentmentioning
confidence: 99%
“…Any oral cariogenic bacteria that reside in the dentin tubules or smear layer following restorative work may subsequently multiply and induce secondary caries or pulpal inflammation (da Silva et al 2006). Existing research in this area has confirmed that residual bacteria can proliferate from the smear layer beneath the restoration, leading to irritation and inflammation (Meiers and Shook 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Residual bacteria on the dentin surface due to incomplete removal of caries are a potential problem in restorative dentistry. 1 According to Brannstrom, possible sources of infection in a prepared cavity are bacterial microleakage, bacteria present in the smear layer, in dentinal tubules, at the dentino-enamel junction and bacteria recontaminating the prepared cavity prior to placing a restoration. 2 Tissue fluids from the pulp and the organic content of dentin provide sufficient substrate for microbial growth under restorations.…”
Section: Introductionmentioning
confidence: 99%